A FISIOTERAPIA NA UNIDADE DE TERAPIA INTENSIVA - PRZYCZYNSKI, TAÍS E.; MAURER, BRUNA D. P.; EICKHOFF, HELOÍSA; SFALCIN, JANAÍNA L.; WINDMÖLLER, POLLYANA; PILLA, SABRINA (Salão do Conhecimento, 2013)
Resumo